RNA Degradation in Saccharomyces cerevisae - Parker, Roy (Genetics (Austin), 2012)
All RNA species in yeast cells are subject to turnover. Work over the past 20 years has defined degradation mechanisms for messenger RNAs, transfer RNAs, ribosomal RNAs, and noncoding RNAs. In addition, numerous quality control mechanisms that target aberrant RNAs have been identified. Generally, each decay mechanism contains factors that funnel RNA substrates to abundant exo- and/or endonucleases. Key issues for future work include determining the mechanisms that control the specificity of RNA degradation and how RNA degradation processes interact with translation, RNA transport, and other cellular processes.